Caring for Childbearing Women in Crisis: Midwife Pilgrim. Issue 5 (September 2017) - Callister, Lynn Clark
Abstract : As perinatal nurses, there are many opportunities to serve others and make a difference. Our global health nursing expert, Dr. Callister, discusses Midwife Pilgrim, one organization working to help women and child in disaster prone areas of the world.